Postnatal Brain Growth Patterns in Pontocerebellar Hypoplasia - van Dijk, Tessa; Barth, Peter; Baas, Frank; Reneman, Liesbeth; Poll-The, Bwee Tien (Neuropediatrics, 2020)
Background Pontocerebellar hypoplasia (PCH) is a rare group of disorders mainly affecting the cerebellum and pons. Supratentorial structures are variably involved. We assessed brain growth patterns in patients with the most frequent forms of PCH, namely PCH1B (OMIM#614678) and PCH2A (OMIM#277470), since in these types of PCH, pre- and postnatal neurodegeneration is established by neuropathological profiling. To assess the influence of the different pathomechanisms on postnatal growth patterns, we included CASK-associated microcephaly and PCH (MICPCH, OMIM#300749) patients in our analyses, as MICPH mimics PCH on magnetic resonance imaging (MRI) but represents a developmental disorder including abnormal neuronal migration.Methods A total of 66 patients were included: 9 patients with PCH1B, 18 patients with PCH2A, 6 patients with MICPCH, and 33 age- and gender-matched hospital-based controls. Segmentation of the vermis and cerebellum was performed manually, as were measurements of the thickness of the head of the caudate nucleus, the width of the anterior horn, and lateral ventricle size.Results The cerebellum was severely hypoplastic at birth in all patients, and postnatal growth was nearly absent. In patients with PCH1B/2A, we found relative sparing of the vermis compared with the cerebellar hemispheres. In addition, PCH1B and PCH2A cases demonstrated thinning of the head of the caudate nucleus, an associated increase in anterior horn width, and an increase in lateral ventricle size. None of these features were seen in the MICPCH group.Conclusions Our findings confirm the progressive nature including caudate nucleus atrophy in PCH1B and PCH2A. In MICPCH, the relative sparing of supratentorial structures confirms its different pathomechanism.
Keywords: pontocerebellar hypoplasia; CASK mutations; cerebellum; pons; caudate nucleus; brain volumetry; MRI